Poster No. 116 Hemodynamic characteristics associated with partial thrombosis of the false lumen in patients with chronic aortic dissection of the descending aorta: a 4D flow CMR study. (21st October 2022) - Muñoz, Aroa Ruiz; Guala, Andrea; Dux-Santoy, Lydia; Teixidó-Turà, Gisela; Garrido-Oliver, Juan; Garcia-Duran, Ana; Valente, Filipa; Galian-Gay, Laura; Gutierrez, Laura; Cuellar-Calabria, Hug; Johnson, Kevin; Wieven, Oliver; et al.
Abstract: Background: Partial thrombosis of the false lumen (FL) in patients with chronic aortic dissection (AD) of the descending aorta has been associated with faster aortic dilation. Four-dimensional phase-contrast cardiovascular magnetic resonance (4D flow CMR) studies analyzing flow dynamics and biomechanics in the FL and their relationship with partial thrombosis are lacking. This study aimed to compare FL flow dynamics and biomechanics between patients with a patent and partially thrombosed FL. Materials and methods: Patients with a chronic, patent (no thrombus) or partially thrombosed FL in the descending aorta after an AD underwent an imaging follow-up including a magnetic resonance angiography (MRA) and a 4D flow CMR study. FL thrombosis was quantified as the ratio of thrombus volume and FL volume on MRA. FL flow dynamics was assessed in terms of forward flow, wall shear stress (WSS), maximum kinetic energy (KE) and acceleration, and flow stasis on 4D flow CMR. Aortic stiffness in the FL was quantified using pulse wave velocity (PWV). Results and conclusions: Sixty-five patients with a complete imaging protocol were included in the study (patency in 34 patients, partial thrombosis in 31). Partial thrombosis of the FL was associated with a reduction in the amount and energy of flow in the FL (reduced forward systolic flow, KE and acceleration), and a more stagnated flow in the FL (increased flow stasis). Axial WSS showed a tendency to be lower in the partial thrombosis group compared to the patency group, while PWV were similar in both of them. Funding: IJC2018-037349-I.